KERJASAMA GARUDA FOOD INDONESIA DENGAN SUNTORY BEVERAGE AND FOOD DALAM BIDANG INDUSTRI MAKANAN DAN MINUMAN RINGAN DI INDONESIA - Pratiwi, Puspa; Rani, Faisyal (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Indonesia is one of the developings country that make cooperation with others country. Economic cooperation in form of foreign investment is one of the cooperation.This research is aim to explain about economic cooperation between Garudafood and Suntory Bevarage and Food in snacks and drinks industry in Indonesia.This research is using qualitative methods and has theoretically built by using International Cooperation Theory as the main theory and Foreign Direct Investment Theory as the second theory. Researcher has gather the datas from book, mass media, encyclopedia, and website to analyse the international economic cooperation between the two industry.Researcher has formulated the hypothesis wich revealed the fact that the economic cooperation between Indonesia's Garudafood and Japan's Suntory bevarage and food is in the form of joint venture by built joint venture company, Suntory Garuda.Key words : Joint venture, investment, Suntory beverage and food, garuda food, economic coorporation